Intriguing Role of Proline in Redox Potential Conferring High Temperature Stress Tolerance - Kavi Kishor, P. B.; Suravajhala, Prashanth; Rathnagiri, P.; Sreenivasulu, Nese (Frontiers in Plant Science, 2022)
Proline is a proteinogenic amino acid synthesized from glutamate and ornithine. Pyrroline 5-carboxylate synthetase (P5CS) and pyrroline 5-caroboxylate reductase (P5CR) are the two key enzymes involved in proline synthesis from glutamate. On the other hand, ornithine-δ-aminotransferase (OAT) converts ornithine to pyrroline 5-carboxylate (P5C), an intermediate in the synthesis of proline as well as glutamate. Both proline dehydrogenase (ProDH) and P5C dehydrogenase (P5CDH) convert proline back to glutamate. Proline accumulation is widespread in response to environmental challenges such as high temperatures, and it is known to defend plants against unpropitious situations promoting plant growth and flowering. While proline accumulation is positively correlated with heat stress tolerance in some crops, it has detrimental consequences in others. Although it has been established that proline is a key osmolyte, its exact physiological function during heat stress and plant ontogeny remains unknown. Emerging evidence pointed out its role as an overriding molecule in alleviating high temperature stress by quenching singlet oxygen and superoxide radicals. Proline cycle acts as a shuttle and the redox couple (NAD+/NADH, NADP+/NADPH) appears to be highly crucial for energy transfer among different cellular compartments during plant development, exposure to high temperature stress conditions and also during the recovery of stress. In this review, the progress made in recent years regarding its involvement in heat stress tolerance is highlighted.